Business Environment and Cost of Doing Business - Hussain, Abid Abrar; Mir, Aized H.; Durrani, Amer Z.; Zaidi, Hasan A. (World Bank, Washington, DC, 2014)
The objective of the Pakistan Infrastructure Implementation Capacity Assessment (PIICA) study was to identify and ascertain the extent to which certain complex and dysfunctional business processes in fact contribute to the overall delays caused in completion of infrastructure projects. The primary focus was to understand and document the business processes relating to the life cycle of infrastructure projects, especially processes that involve an interface with external agencies. The study was further extended to assess the resultant impact of the delays caused on overall capacity, efficiency, and costs of the project. The study identifies areas that contain business processes and which relative to other processes in the life cycle of a project are disproportionate, or a cause of significant time delays in completion of such projects. Such disproportionate business processes that are unpredictable and vary greatly from the planned time or inputs are areas that can be the focus for selective and further analysis, process re-engineering and recommendations. Such areas can be targeted to improve the overall business and regulatory environment applicable to players and stakeholders relevant to infrastructure projects. The study identifies that corruption in the overall environment exists which over time has become embedded and is accepted as necessary, if a project is to be successfully won and then executed with minimum hindrances from the government. These practices cannot be called business processes but are an integral and unavoidable reality of the current business environment. The PIICA study highlights: (i) the business processes and relative time and effort required at different steps during a project life cycle, under normal or prevailing business environment in the country; (ii) the business processes and relative time and effort required at different steps during a project life cycle, under normal or prevailing business environment in the country; and (iii) the defined and undefined procedures that exist, many of which are not stated in contract documents, neither in project plans nor subjected to risk analysis and risk mitigation at the outset. These appear to render the best of project time lines and budgeted plans as mere estimates.